Comparative Evaluation of the Effect of Chlorhexidine Gluconate, Raw Propolis and Hydrogen Peroxide on Dental Plaque and Gingival Inflammation - Porwal, Surbhi; Mathur, Aditi; Shetty, Neema; Manohar, Balaji; Makhijani, Barkha; Mundra, Rohit (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Plaque is the soft deposit that forms the biofilm consisting of microorganisms adhering to the tooth surface and is proved beyond doubt to be the initiator of gingival and periodontal disease. Plaque control is the mainstay in periodontal disease. Aim: To compare the effect of 0.2% chlorhexidine gluconate, raw propolis and 3% hydrogen peroxide mouthwash on dental plaque and gingival inflammation. Materials and Methods: Thirty subjects in the age group of 20-40 years were enrolled in the study. Plaque index and Modified Gingival Index were recorded at baseline and oral prophylaxis was performed. Subjects were then randomly divided into three groups (n=10) and were asked to rinse with 10ml mouthwash twice daily for 15 days. Group I received 0.2% chlorhexidine gluconate mouth wash, Group II raw propolis diluted with distilled water (1:1), and Group III 3% hydrogen peroxide (1:1) mouthwash. Subjects were recalled on 7 day and 28 day for re-evaluation and recording plaque index and modified gingival index. Statistical analysis was done to evaluate the efficacy of all the three mouthwashes. Results: The results showed that all the three mouthwashes were effective in reducing plaque and gingival inflammation. Chlorhexidine gluconate 0.2% showed to be the most effective in reduction of dental plaque. Propolis was observed to be the most effective in reducing gingival inflammation over a period of 28 days. Conclusion: Propolis can be effectively used as a mouthwash without any potential side effects as an alternative to chlorhexidine mouthwash in reducing gingival inflammation.